2004
DOI: 10.1080/02786820490249036
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Measurements of Sub-20 nm Diameter Particle Chemical Composition by Thermal Desorption Chemical Ionization Mass Spectrometry

Abstract: We report the first online measurements of the chemical composition of atmospheric aerosol in the 6-20 nm diameter range. These measurements were performed using the recently developed Thermal Desorption Chemical Ionization Mass Spectrometer (TDCIMS), and were made possible by recent sensitivity enhancements resulting from (a) the development of a unipolar charger optimized for high aerosol flow rates, and (b) an improved flow system in the TDCIMS sample inlet. Measurements of atmospheric aerosol in Boulder, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
181
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(190 citation statements)
references
References 25 publications
6
181
1
2
Order By: Relevance
“…For example, aliphatic amines contributed 23% to the NPF events at a remote forested site in Hyytiala, Finland in March, 2006 and 47% to that at an urban site in Tecamac, Mexico in April, 2007. 12 Amines observed in Marshall Field Site, Colorado (2007), 13 North Boulder, Colorado (2009), and Atlanta, Georgia (2009) 14 have also been confirmed to play the same role in NPF events. 12 In laboratory studies, NPF was observed when amines were added into a smog chamber or flow tube reactor containing a certain concentration of nitric acid, 15 sulfuric acid, 16 or methanesulfonic acid (MSA).…”
Section: ■ Introductionmentioning
confidence: 90%
“…For example, aliphatic amines contributed 23% to the NPF events at a remote forested site in Hyytiala, Finland in March, 2006 and 47% to that at an urban site in Tecamac, Mexico in April, 2007. 12 Amines observed in Marshall Field Site, Colorado (2007), 13 North Boulder, Colorado (2009), and Atlanta, Georgia (2009) 14 have also been confirmed to play the same role in NPF events. 12 In laboratory studies, NPF was observed when amines were added into a smog chamber or flow tube reactor containing a certain concentration of nitric acid, 15 sulfuric acid, 16 or methanesulfonic acid (MSA).…”
Section: ■ Introductionmentioning
confidence: 90%
“…According to the classical ternary homogeneous theory developed recently, the presence of ammonia in partsper-trillion levels significantly enhances nucleation rates (Yu et al, 2006). Many field measurements and laboratory simulations have corroborated the crucial role of ammonia in the growth of newly formed particles (Smith et al, 2004;Sakurai et al, 2005;Gaydos et al, 2005). Though experimental evidence seems very limited, nitrate has been reported as a crucial contributor to nanoparticle growth, especially for 10-30 nm particles where nitrate is dominant (Hildebrandt et al, 2012).…”
Section: Insights Into the Chemical Species Involvedmentioning
confidence: 99%
“…Gaseous sulfur has proved to play a vital role in the nucleation process (Petäjä et al, 2009;Kulmala et al, 2013). Atmospheric ammonia can effectively lower the surface pressure of gaseous sulfuric molecular and participates in homogeneous nucleation with gaseous sulfuric acid and water vapor (Smith et al, 2004;Sakurai et al, 2005;Gaydos et al, 2005). In addition, there are other species responsible for NPF such as amines (Yu et al, 2012;Benson et al, 2011), low-volatility organic vapors Paasonen et al, 2010;Riipinen et al, 2011;Ehn et al, 2014) and iodine compounds (O'Dowd et al, 2002;Vuollekoski et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As a sensitive, selective, and soft-ionization measurement technique, chemical ionization mass spectrometry (CIMS) has received significant use in the real-time in situ measurement of atmospheric trace species (Huey et al, 1995;Fortner et al, 2004;Hearn and Smith, 2004;Smith et al, 2004;Crounse et al, 2006;Huey, 2007;Veres et al, 2008;Kercher et al, 2009;Zhao et al, 2010). The recent coupling of chemical ionization to high-resolution time-of-flight mass spectrometers (HR-ToF-MS) enables the simultaneous determination of the abundance and molecular composition of a wide array of atmospheric inorganic and organic compounds with fast time response and high sensitivity (Junninen et al, 2010;Bertram et al, 2011;Yatavelli et al, 2012;Aljawhary et al, 2013;Lee et al, 2014;Lopez-Hilfiker et al, 2014, 2016aFarmer, 2015, 2016;Yuan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%